2020
DOI: 10.1101/gad.339317.120
|View full text |Cite
|
Sign up to set email alerts
|

miR760 regulates ATXN1 levels via interaction with its 5′ untranslated region

Abstract: Identifying modifiers of dosage-sensitive genes involved in neurodegenerative disorders is imperative to discover novel genetic risk factors and potential therapeutic entry points. In this study, we focus on Ataxin-1 (ATXN1), a dosage-sensitive gene involved in the neurodegenerative disease spinocerebellar ataxia type 1 (SCA1). While the precise maintenance of ATXN1 levels is essential to prevent disease, the mechanisms that regulate ATXN1 expression remain largely unknown. We demonstrate that ATXN1's unusuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 51 publications
0
27
1
Order By: Relevance
“…MicroRNAs (miRNAs or miRs) are short, single-stranded non-coding RNA molecules with a length of about 22 nucleotides that can directly combine with the 3′-UTR of their target mRNAs to induce their degradation or inhibit their translation [ 1 ]. Some studies have shown that miRNAs can also play a regulatory role on gene transcription by binding to the 5′UTR of a target gene [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Their roles in cancer may also be related to tumor inhibition or carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs or miRs) are short, single-stranded non-coding RNA molecules with a length of about 22 nucleotides that can directly combine with the 3′-UTR of their target mRNAs to induce their degradation or inhibit their translation [ 1 ]. Some studies have shown that miRNAs can also play a regulatory role on gene transcription by binding to the 5′UTR of a target gene [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Their roles in cancer may also be related to tumor inhibition or carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, ATXN1 dynamics are altered by the Gln expansion and failure in nuclear export upon polyQ expansion dramatically reduces the retro-transport into the cytoplasm [ 61 ]. Regardless of the polyQ expansion, subtle increases in wild type ATXN1 levels could also lead to SCA1 hallmarks [ 62 ], whereas decreasing ATXN1 expression helps to reduce ATXN1’s accumulation and mitigates cerebellar SCA1 pathogenesis [ 63–66 ]. Conversely, it also has been shown that loss of the protein increases the levels of BACE1 and Aβ pathology, indicating that ATXN1 levels is a potential factor for AD development [ 67 ].…”
Section: Ataxin-1 (Atxn1) and Ataxin-8 (Atxn8)mentioning
confidence: 99%
“…Conversely, it also has been shown that loss of the protein increases the levels of BACE1 and Aβ pathology, indicating that ATXN1 levels is a potential factor for AD development [ 67 ]. Co-regulation by microRNAs (miRNAs) together with the RNA-binding protein PUMILIO1 (PUM1) are shown to fine-tune posttranscriptionally ATXN1 mRNA levels [ 62 , 63 , 68 ]. Posttranslational modifications such as phosphorylation, transglutamination, ubiquitination, and sumoylation are also required for the ATXN1 function [ 60 ].…”
Section: Ataxin-1 (Atxn1) and Ataxin-8 (Atxn8)mentioning
confidence: 99%
“…Previous studies showed that the polyQ-expansion stabilizes ATXN1, leading to its toxic accumulation in the nucleus of affected neurons (7,8). Attempts to decrease ATXN1 levels have since been shown to mitigate the cerebellar SCA1 phenotypes in mice (9)(10)(11)(12). One strategy to lower ATXN1 levels is by modulating the phosphorylation of serine 776 (S776) in ATXN1 (9,13).…”
Section: Introductionmentioning
confidence: 99%